High prevalence of food taboos and dietary restrictions in lactating mothers from coastal districts of a south Indian state: a hospital based study - Kudumula, Vikram; Maram, Krishna Prasad; Nukala, Bavana; Paturi, Venkata Rama Rao (International Journal Of Community Medicine And Public Health, 2021)
Background: Adequate nutrition during pregnancy and lactation is pivotal for wellbeing of newborn infants. However, presence of traditional beliefs and taboos associated with food intake during pregnancy and lactation could interfere with nutritional needs of growing infants resulting in a variety of nutritional disorders. Our objective was to study the prevalence of dietary restrictions and food taboos practiced by lactating women from five costal districts of the state of Andhra Pradesh, India. Methods:It was a descriptive and observational study, conducted between November 2020 to January 2021 at the Children’s Heart Institute, Andhra Hospitals, Vijayawada, Andhra Pradesh. The study was conducted on mothers attending the out-patient clinic of pediatric cardiology department using convenient sampling technique. A pretested questionnaire was used to collect the data. Results: A total of 161 mothers have participated in the survey and, almost all of them (99.3%) have restricted one or more food item during lactation. Age of the mother, level of education and socio-economic status have no bearing on the prevalence of food restrictions and food taboos. Most commonly restricted food items include sweets, fruits, leafy vegetables, yogurt, some pulses, eggs and nuts. The concept of hot and cold food items is highly prevalent in the study population and lactating mothers have no knowledge of the nutritive value of the foods avoided/restricted. Conclusions:Food restrictions and taboos associated with food intake during post-partum period are widespread in our study population. Improving girl child education and campaigning through print and digital media are important tools in fighting against harmful traditional practices interfering with adequate nutrition during pregnancy and lactation.